Design for regression models with correlated errors - Dette, Holger; Pepelyshev, Andrey; Zhigljavsky, Anatoly (Technische Universität Dortmund, 2012)
The present article is a draft of a chapter in the Handbook of Design and Analysis of Experiments and provides a survey of results on experimental design for linear regression models with correlated responses.
Discussion Paper / SFB 823;58/2012
Keywords: 310; 330; 620